Comparison and Evaluation of Ticarcillin and Carbenicillin Using Disk Diffusion Methods - Parry, Michael F. (1976)
Ticarcillin has proved to be two- to fourfold more active than carbenicillin against most strains of Pseudomonas aeruginosa. Although susceptibility of the Enterobacteriaceae to ticarcillin could be predicted from results obtained with carbenicillin disks, neither the 50-μg nor the 100-μg carbenicillin disk proved suitable for testing susceptibility of P. aeruginosa to ticarcillin. Forty-three percent of Pseudomonas strains judged to be resistant to carbenicillin by the 100-μg carbenicillin disk were susceptible to ticarcillin by agar dilution studies. Results obtained with a 75-μg ticarcillin disk showed excellent correlation between zone size and ticarcillin minimal inhibitory concentration values and produced good discrimination between resistant and susceptible strains of Pseudomonas as determined by agar dilution studies. Using a 75-μg ticarcillin disk, a zone size of 12 to 14 mm was appropriate for designating intermediate susceptibility, and a zone greater than or equal to 15 mm was appropriate for designating susceptible strains of both P. aeruginosa and the Enterobacteriaceae.